1966
DOI: 10.1177/004051756603600908
|View full text |Cite
|
Sign up to set email alerts
|

Spinning of Polyamides from Sulfuric Acid Solution

Abstract: Increasing the aromatic ring content of polyamides results in increased melting points and fiber stiffness. These intractable polymers generally cannot be melt-spun or solutionspun from conventional spinning solvents. A search for general classes of solvents for intractable polyamides resulted in the conclusion that the solvent must act as a sufficiently strong Lewis acid to complex the polymer and have sufficient solvent power to dissolve the resulting complex. Examples are given of this two-step mechanism fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1970
1970
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Highly negative interaction parameters between solvent and polymer were also reported by Cheng [9] and Bulte [31] for the formic acid-Nylon systems. It was claimed that hydrogen bonding and protonation effects [32,33] are responsible for the strong interaction forces between these molecules. The interaction parameter between water and EVAL was treated as being concentration independent since Eq.…”
Section: Phase Behavior Of Water-dmso-eval At 25°cmentioning
confidence: 99%
“…Highly negative interaction parameters between solvent and polymer were also reported by Cheng [9] and Bulte [31] for the formic acid-Nylon systems. It was claimed that hydrogen bonding and protonation effects [32,33] are responsible for the strong interaction forces between these molecules. The interaction parameter between water and EVAL was treated as being concentration independent since Eq.…”
Section: Phase Behavior Of Water-dmso-eval At 25°cmentioning
confidence: 99%
“…Rosenthal [42] for nylons in sulfuric acid. These authors' results differ from Knudgen's [43] results for polyacrylonitrile fibers where coagulation bath temperature was the controlling factor.…”
Section: Circumfrential Bandsmentioning
confidence: 99%
“…These authors' results differ from Knudgen's [43] results for polyacrylonitrile fibers where coagulation bath temperature was the controlling factor. Epstein and Rosenthal [42] interpreted this phenomenon to indicate that, in nylons, coagulation from sulfuric acid occurred by deprotonation -an acid base reaction. This is also a plausible explanation in the present system based upon the work of Shen et al [7] who showed by spectroscopic analysis that PBT model compounds were highly protonated in MSA solution.…”
Section: Circumfrential Bandsmentioning
confidence: 99%
“…More importantly, the phenomenon of macrovoid formation is of great significance even for normal textile fibers made by wet spinning. 2, [23][24][25] Membrane scientists are divided on the origins of macrovoid formation. Several believe that it most likely originates from thermodynamics, so they have investigated the subject from the perspective of chemical potential gradients and phase diagrams with the aid of the Flory-Huggins theory.…”
Section: Introductionmentioning
confidence: 99%